SEKSUALITAS DALAM PERNIKAHAN MENURUT 1 KORINTUS 7:1-5 - Manase Gulo (Manna Rafflesia, 2018)
Sexuality is God's plan for Christian marriage. But not a few deviations occur in the marriage of believers, irregularities occur because of misunderstanding the meaning of sexuality in marriage, namely in terms of assessment and application. This deviation can be found in the Corinthian church which is a very serious problem. Therefore it is very important to examine the principles of sexuality in marriage, one of the Apostle Paul's answers to the problem is in Chapter 1 Corinthians 7: 1-5, therefore to make an important contribution to understanding sexuality in marriage for believers, it is necessary to make review of exegetical studies.